2015
DOI: 10.1136/bmj.h4023
|View full text |Cite
|
Sign up to set email alerts
|

A patient request for some “deprescribing”:

Abstract: A 52 year old man with a history of type 2 diabetes for 14 years and hypertension for nine years presented to his general practitioner. He was a non-smoker with an alcohol intake of eight units a week. He had been experiencing bloating, abdominal pains, and erratic motions for more than a year. Because he drove about 12 000 miles a year for his job he found the loose motions "a real worry." He wondered whether any of his problems might be caused by his drugs and asked if he could cut down on any if they weren'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In another randomised weight intervention trial, Mayer et al reported that weight loss among subjects undertaking either a low-carb or a low-fat diet was similar, but those on a low-carb diet also benefited from an improved glycaemic control and a significant antiglycemic drug dose reduction [ 7 ]. Similar reports of “deprescribing” antidiabetic medications have been reported in patients with type 2 diabetes undertaking intensive lifestyle change programs [ 12 ].…”
Section: Discussionsupporting
confidence: 68%
“…In another randomised weight intervention trial, Mayer et al reported that weight loss among subjects undertaking either a low-carb or a low-fat diet was similar, but those on a low-carb diet also benefited from an improved glycaemic control and a significant antiglycemic drug dose reduction [ 7 ]. Similar reports of “deprescribing” antidiabetic medications have been reported in patients with type 2 diabetes undertaking intensive lifestyle change programs [ 12 ].…”
Section: Discussionsupporting
confidence: 68%
“…A case review by Unwin and Tobin 8 documented that they were able to ‘deprescribe’ a 52-year-old man who was living with T2D for 14 years. He was suffering from gastrointestinal side effects from his metformin medication.…”
Section: Discussionmentioning
confidence: 99%
“…Following a low-carbohydrate diet, the patient steadily lost a total of 16 kg over 7 months and successfully stopped all prescribed drugs, thereby achieving his goal of being medication-free. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Showcasing n=1 cases may also provide motivation to colleagues, helping them to challenge preconceived ideas and consider the difference between research and clinical practice, then to think through and apply similar approaches to help their own patients-ultimately leading to better practice. 4 However, these views are not dichotomous, but complementary, whereby practice should inform science and science should inform practice.…”
Section: Bridging the Gap Between Science-led Research And Evaluationmentioning
confidence: 99%